Halal Industry: A literature Bibliometric Review on Halal Studies - Darmawati, Darmawati; Hardiana, Dian; Mainata, Dedy; Nuryadin, Muhammad Birusman (Mazahib, 2023)
The halal industry has become the fastest-growing global business and has reached 1.8 billion consumers globally with an estimated value of USD 2.1 trillion and has become the main focus for developing halal recognition processes or regulatory agencies in making the halal industry growth. This study aims to find out the most influential writers and what issues are most explored in the halal industry, the pattern of halal industry research, which countries and their relationship with publications can be used as benchmarks for further research, present findings from the most written articles, and provide direction for further research on the theme of the Halal Industry. This study quantitatively analyzes the literature on the halal industry, represented by 141 English articles from the Scopus database from 2009 to 2022. By using a bibliometric approach plus content analysis. This study found that Malaysia was the most relevant country: The University of Technology MARA is the most relevant institution, International Journal of Supply Chain Management, the Journal of Islamic Marketing, Malaysian Journal of Consumer and Family Economics, and Pertanika Journal of Social Sciences and Humanities. There are three main clusters of research: (1) Halal Business, (2) Halal Industry and Tourism, and (3) Halal Marketing and Certification.